2020
DOI: 10.1039/d0ce00315h
|View full text |Cite
|
Sign up to set email alerts
|

New pronounced progress in the synthesis of group 5 polyoxometalates

Abstract: This highlight summarizes new developments made in group 5 polyoxometalate science of high nuclearity clusters with focus on synthetic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 124 publications
0
21
0
Order By: Relevance
“…The group 5 and 6 polyoxometalates (POMs) build cage like cluster anions composed of {MO 6 } octahedra (M=V, Nb, Ta, Mo and W), while V is often observed in a rectangular‐pyramidal VO 5 coordination [1–17] . Polyoxoniobates (PONbs) as a subgroup of POMs exhibit an impressive structural diversity, represented by e. g. the Lindqvist {Nb 6 O 19 } 8− , [18–21] the decaniobate {Nb 10 O 28 } 6− , [22–24] the Keggin {XNb 12 O 40 } n− (X=P, Si, Ge, V) clusters, [25–27] and giant cluster shells like {Nb 114 } [28] or {Nb 288 } [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The group 5 and 6 polyoxometalates (POMs) build cage like cluster anions composed of {MO 6 } octahedra (M=V, Nb, Ta, Mo and W), while V is often observed in a rectangular‐pyramidal VO 5 coordination [1–17] . Polyoxoniobates (PONbs) as a subgroup of POMs exhibit an impressive structural diversity, represented by e. g. the Lindqvist {Nb 6 O 19 } 8− , [18–21] the decaniobate {Nb 10 O 28 } 6− , [22–24] the Keggin {XNb 12 O 40 } n− (X=P, Si, Ge, V) clusters, [25–27] and giant cluster shells like {Nb 114 } [28] or {Nb 288 } [29] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, infinite chains present in the structures of VF 5 and MX 4 (M = Nb, Ta; X = Cl, Br, I); VS 4 , V 2 Se 9 , Nb 2 Se 9 ; infinite layers in NbF 4 , MQ 2 (M = V, Nb, Ta Q = S, Se, Te), MQ 3 (M = Nb, Ta, Q = S, Se); NbTe 4 , and TaTe 4 . V, Nb, and Ta are known to form polyoxometallate compounds; a large class of cluster compounds is also developed …”
Section: Introductionmentioning
confidence: 99%
“…Polynuclear vanadium compounds are mainly represented by polyoxovanadates of different nuclearities and structures. ,, Polynuclear niobium and tantalum compounds are presented as polyoxometallates and also cluster complexes with bridging halogen atoms . Besides V 4 S 9 Br 4 , a few examples of polynuclear Group 5 TMCHs are compounds Ta 4 S 9 Br 8 and Ta 4 Se 9 I 8 as well as O-centered complexes Nb 4 OTe 9 I 4 and Ta 4 OTe 9 I 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the research groups of Wang, Yang, Niu, Zheng, Zhao, etc., have constructed a series of high-nuclear transition-metal (TM)-substituted POTs by using {XW 9 } as precursors since 2006. In the last year, Suzuki et al reported a couple of organic–inorganic POMo-based monomer, dimer, and tetramer architectures by reacting {PMo 9 } building units with pyridyl, 4,4′-bipyridyl, and porphyrin ligands, respectively . Polyoxovanadate (POV) has also been an intriguing subfamily in the POM field for the benefit of vanadium itself, carrying versatile valent states (+V, +IV, +III, or mixed oxidation states) and coordination geometries (VO n , n = 4–6) . However, the structural diversity of POVs is significantly lower compared to its peers, like POTs and POMos, which might be largely due to the lack of lacunary POV precursors.…”
mentioning
confidence: 99%